The Association Between Resting State Functional Connectivity and the Trait of Impulsivity and Suicidal Ideation in Young Depressed Patients With Suicide Attempts - Cao, Jun; Chen, Xiaorong; Chen, Jianmei; Ai, Ming; Gan, Yao; He, Jinglan; Kuang, Li (Frontiers in Psychiatry, 2021)
Suicide is a leading cause of death among youth and is strongly associated with major depressive disorder (MDD). However, the neurobiological underpinnings of suicidal behaviour and the identification of risk for suicide in young depressed patients are not yet well understood. In this study, we used a seed-based correlation analysis to investigate the differences in resting-state functional connectivity (RSFC) in depressed youth who had or did not have a history of suicide attempts and healthy controls (HCs). Suicidal attempters (ATT group, n=35), non-suicide attempters (NAT group, n=18), and HCs significantly differed from each other in the RSFC patterns with the left superior prefrontal gyrus (L-SFG) and left middle prefrontal gyrus (L-MFG) as the regions of interest (ROIs). The ATT group showed decreased RSFC of the left middle frontal gyrus with the left superior parietal gyrus compared to the NAT and HC groups. Decreased RSFC between the left superior frontal gyrus and the right anterior cingulate cortex (rACC) was found in the ATT group compared to the NAT and HC groups. Furthermore, the left prefrontal-parietal connectivity was associated with suicidal ideation and levels of impulsivity, but RSFC of the left prefrontal cortex with the rACC was correlated only with impulsivity levels and was not related to suicidal ideation in the ATT group. Our results demonstrated that altered RSFC of the prefrontal-parietal and prefrontal-rACC regions was associated with suicide attempts in depressed youth, and state-related deficits in their interconnectivity may contribute to traits such as cognitive impairments and impulsivity to facilitate suicidal acts. Our findings might suggest that the neural correlates of suicidal behaviours might be dissociable from those related to the severity of current suicidal ideation. There may be different neural circuits underlying suicide attempts from those that underlie suicidal ideation.